29Si AND 27Al CPMAS NMR QUALITATIVE AND QUANTITATIVE ANALYSIS OF KAOLINITE AND DICKITE IN KOS ISLAND KAOLINS, GREECE - Papoulis, D. (Bulletin of the Geological Society of Greece, 2007)
The application of 27Al and 29Si CPMAS NMR spectroscopy to the investigation of selected /caolinite and dickite bearing samples from hydrothermally altered rhyolites of Kos island is tested using also XRD and analytical SEM-EDS data. Kaolinite and dickite, can be detected by both their tetrahedral Si and octahedral Al CPMAS NMR spectra. It was found that the interference of the peaks become less significant and the shape of the peaL· narrow when the pulse recycling delay is high (up to 10s). The octahedral Al / tetrahedral Si ratios of kaolinite group mineral forms from samples showing various degrees of alteration, calculated from the NMR spectra, were found to be very similar to these derived from the structural formulae of SEM-EDS microanalyses. In this work it is presented for the first time an approach to provide narrow CPMAS NMR peaks. The narrow shape of the peaks provides accurate measurements of the exact position of the peaL· and the octahedral Al / tetrahedral Si ratios.